PENGARUH RETURN ON ASSETS (ROA), DEBT TO EQUITY RATIO (DER) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PADA PT ADHI KARYA TBK PERIODE 2014-2022 - Setiawan, Erik; Sanjaya, Rudi (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Return On Assets, Debt to Equity Ratio, and Price Earning Ratio on the stock price of PT. Adhi Karya Tbk from 2014 to 2022, both partially and simultaneously. The research method and data type used were descriptive quantitative and secondary data, with the sample consisting of financial statements including balance sheets and income statements of PT. Adhi Karya Tbk from 2014 to 2022. The data analysis method employed classical assumption tests and linear regression. Hypothesis testing was conducted using t-tests, F-tests, and Coefficient of Determination. The findings reveal that Return On Assets (ROA) partially influences the stock price of PT Adhi Karya Tbk for the period 2014-2022. Debt to Equity Ratio (DER) partially does not affect the stock price of PT Adhi Karya Tbk for the period 2014-2022, and Price Earning Ratio (PER) partially does not influence the stock price of PT Adhi Karya Tbk for the period 2014-2022. Simultaneously, Return On Assets (ROA), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) affect the stock price of PT Adhi Karya Tbk for the period 2014-2022. The Coefficient of Determination indicates that 77.7% of the Stock Price is explained by Return On Assets (ROA), Debt to Equity Ratio (DER), and Price Earning Ratio (PER), while the remaining 22.3% is influenced by other variables.